2020
DOI: 10.3960/jslrt.19038
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate-associated lymphoproliferative disorder demonstrating composite lymphoma of EBV-negative diffuse large B-cell lymphoma and EBV-positive mucocutaneous ulcer

Abstract: Other iatrogenic immunodeficiency-associated lymphoproliferative disorders (Oiia-LPD) has been defined as lymphoproliferative disorders or lymphomas developing in patients receiving immunosuppressive drugs for autoimmune diseases or conditions other than in the post-transplant setting. 1 In particular, many rheumatoid arthritis (RA) patients are treated using methotrexate (MTX). The pathological features of MTX-LPD vary. Histology of diffuse large B-cell lymphoma (DLBCL) is predominant, followed by that of cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…In 186 EBVMCU cases [ 5 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ], during the follow-up periods (1–180 months), spontaneous improvement of the ulcers was noted in eight patients, and 126 patients had either complete or partial remission after discontinuation or dose reduction of immunosuppressants, chemotherapy, or radiotherapy. While eight patients experienced recurrence [ 15 , …”
Section: Clinical Findings For Ebvmcumentioning
confidence: 99%
“…In 186 EBVMCU cases [ 5 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ], during the follow-up periods (1–180 months), spontaneous improvement of the ulcers was noted in eight patients, and 126 patients had either complete or partial remission after discontinuation or dose reduction of immunosuppressants, chemotherapy, or radiotherapy. While eight patients experienced recurrence [ 15 , …”
Section: Clinical Findings For Ebvmcumentioning
confidence: 99%
“…We reported one case of composite lymphoma associated with MTX-LPD that included both EBVMCU in the pharynx and EBV-negative DLBCL with systemic lymphadenopathy ( Table 2B , Case 6). 27 The pharyngeal lesion disappeared after the discontinuation of MTX, although systemic lymphadenopathy remained. Identification of the site of proliferation of EBV-positive large B-cells in the setting of MTX-LPD is another important feature.…”
Section: Discussionmentioning
confidence: 98%
“…4 Consequently, chemotherapy was advocated in cases in which the exclusive reliance on MTX discontinuation for achieving regression was deemed impractical. 16 Within the spectrum of available regimens, those incorporating rituximab have been endorsed specifically for cases manifesting lymphoma recurrence or progression with the alternative benefit of covering incidental lymphoma. 5,16 Shimada,et al conducted a retrospective study involving Japanese patients and found that rituximab significantly extended both PFS and OS in patients with RA and OIIA LPD compared with those on non-rituximab chemotherapy regimens.…”
Section: Discussionmentioning
confidence: 99%